Effect Of Transparency, Human Resources Competence, Community Participation, Government Internal Control System, Village Apparatur Commitment To Management Village Fund: (Empirical Study on Villages in Meranti Islands District) - Yunni, Yunni; Azlina, Nur; Nurulita, Suci (Lembaga Penelitian dan Pengabdian kepada Masyarkat-Universitas Terbuka, 2022)
This research was conducted with the aim of testing the effect of transparency, human resource competence, community participation, spip and commitment of village officials to the management of village funds. Sources of data used in this study are primary data and questionnaires as a means of collecting research data. The population in this study were 96 villages in Meranti Islands Regency and the number of samples of 77 villages was calculated using the Slovin formula with purposive sampling method, each village there were 6 respondents so that the total respondents were 462 respondents in this study. The statistical results obtained from this study are that transparency and SPIP have an effect on the management of village funds, while the competence of human resources, community participation and commitment of the village apparatus has no effect on the management of village funds.